Real-time auralization of wave simulation in complex three-dimensional acoustic spaces - Raghuvanshi, Nikunj; Snyder, John; Mehra, Ravish; Lin, Ming C.; Govindaraju, Naga (Journal of the Acoustical Society of America, 2011)
A technique has been developed for modeling real‐time sound propagation in static acoustic spaces that relies on pre‐computed wave simulation. The associated system can auralize propagation that includes diffraction, interference, scattering and late reverberation, while supporting tens of moving point sources and moving listener in highly complex three‐dimensional scenes. Since direct storage of simulated impulse responses for runtime use is infeasible, a novel technique was developed to extract and compactly encode the perceptually salient information in the simulated band‐limited impulse responses. The response is automatically broken into early reflections (ERs) and late reverberation (LR), via a threshold on the temporal density of arriving wave‐fronts. The LR is simulated and stored once per room. Detailed spatial variation in ER is simulated, and encoded by a set of peak delays/amplitudes in the time domain and a residual frequency response sampled in octave bands, at each source/receiver point pair on a five‐dimensional grid. An efficient run‐time uses this pre‐computed representation to perform binaural sound rendering based on frequency‐domain convolution. The system demonstrates audible wave‐based effects in real time—diffraction low‐pass filtering behind obstructions, sound focusing (caustics), hollow reverberation in empty rooms, sound diffusion in fully‐furnished rooms, and late reverberation with non‐exponential decay.